2018
DOI: 10.1111/bjh.15108
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib resistance in mantle cell lymphoma: clinical, molecular and treatment aspects

Abstract: Mantle cell lymphoma (MCL) is a lymphoproliferative disorder comprising about 6-10% of all B cell lymphoma cases. Ibrutinib is an inhibitor of Bruton tyrosine kinase (BTK), a key component of early B-cell receptor (BCR) signalling pathways. Although treatment with ibrutinib has significantly improved the outcome of MCL patients, approximately one-third of the patients have primary drug resistance while others appear to develop acquired resistance. Understanding the molecular events leading to the primary and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 94 publications
0
76
0
Order By: Relevance
“…As the advent of ibrutinib, studies have been conducted to unravel the mystery of ibrutinib resistance and clonal evolution in MCL. Some of these newer molecular alterations include: chromosomal complexity, NSD2 , NOTCH2 , UBR5 , BIRC3 , TRAF2 , MAP2K14 , KMT2D , CARD11 , SMARCA4 , and BTK . Activation of PI3K/AKT and the integrin‐β1 signaling pathway has been shown as another mechanism of acquired ibrutinib resistance. Microenvironmental impact —In addition to the pathogenic features described above, the tissue microenvironmental milieu is critical to support MCL cell growth and survival and promote drug resistance.…”
Section: Advances In the Pathogenesis Of MCLmentioning
confidence: 99%
See 1 more Smart Citation
“…As the advent of ibrutinib, studies have been conducted to unravel the mystery of ibrutinib resistance and clonal evolution in MCL. Some of these newer molecular alterations include: chromosomal complexity, NSD2 , NOTCH2 , UBR5 , BIRC3 , TRAF2 , MAP2K14 , KMT2D , CARD11 , SMARCA4 , and BTK . Activation of PI3K/AKT and the integrin‐β1 signaling pathway has been shown as another mechanism of acquired ibrutinib resistance. Microenvironmental impact —In addition to the pathogenic features described above, the tissue microenvironmental milieu is critical to support MCL cell growth and survival and promote drug resistance.…”
Section: Advances In the Pathogenesis Of MCLmentioning
confidence: 99%
“…Overall, the advent of ibrutinib is a “great leap forward” in the treatment of MCL; however, problems with ibrutinib discontinuation, management of ibrutinib‐refractory disease, and mechanisms of ibrutinib resistance pose new challenges. In contrast with SLL/CLL, where the C481S mutation is commonly associated with ibrutinib resistance, this mutation is infrequent in ibrutinib‐resistant MCL, and other mechanisms of ibrutinib resistance and ways to overcome ibrutinib resistance must be explored.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…The mechanisms of ibrutinib resistance and the relevance of clonal evolution are being studied in B cell lymphoid malignancies (Burger et al , ; Jayappa et al , ; Landau et al , ; Zhao et al , ; Hershkovitz‐Rokah et al , ). In contrast to SLL/CLL, where the primary mode of ibrutinib resistance is considered to be via BTK C481S and PLCG2 gene mutations (Ahn et al , ; Woyach et al , ), studies in MCL (Chiron et al , ; Martin et al , ) and in follicular lymphoma (FL) (Jain et al , ) indicate that these mutations were uncommon in ibrutinib‐resistant patients.…”
mentioning
confidence: 99%
“…30,58 However, some MCL and CLL patients are refractory to Ibrutinib treatment. 12,59 Here, we showed that JeKo-1 but not REC-1 MCL cells require BCR signaling for their migration and adhesion to stromal cells, suggesting that Although there is no obvious explanation for the apparent clustering of the MCL patient samples into two separate groups, it is interesting to note that clustering of differentially expressed microenvironment/ adhesion related genes led to separation of MCL patient samples into two groups.…”
Section: Discussionmentioning
confidence: 87%